Perancangan Tata Kelola Teknologi Informasi Event Management Pada Laboratorium Komputer STMIK STIKOM Surabaya - Utami, Sulistia Nofentri; Wurijanto, Tutut; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Computer Laboratory (Labkom) STMIK STIKOM Surabaya supported by the infrastructure of Information Technology (IT) for running the business process services Information Systems and Information Technology (IS/IT). IT infrastructure can’t be separated of an event, such as the reduced capacity of the hard disk server, weakened network speed, decreased of computer performances, and other events. The problem faced Labkom is didn't have event management, so the impact on the delivery of IS/IT services because they still find the user can’t access the website practicum, can’t upload the result of practicum, some softwares can’t run well, and another impacts. Based on these problems need an Event Management then organized and managed so as to produce the Standard Operating Procedures (SOP). This Event Management used by Labkom to prevent the impact of the event so that IS/IT services can be delivered. The SOP design refers to the Policy of Services IS/IT Labkom and ITIL V3 Service Operation phase, particularly on Event Management process. The results of this research are five SOP, eight Work Instructions, nine Work Records which serves to manage events, and Event Management Guide which used as a reference in improving service of Labkom.